Interval Cancers in a Population-Based Screening Program for Colorectal Cancer in Catalonia, Spain - M. Garcia; X. Domènech; C. Vidal; E. Torné; N. Milà; G. Binefa; L. Benito; V. Moreno (Gastroenterology Research and Practice)
Objective. To analyze interval cancers among participants in a screening program for colorectal cancer (CRC) during four screening rounds. Methods. The study population consisted of participants of a fecal occult blood test-based screening program from February 2000 to September 2010, with a 30-month follow-up (n = 30,480). We used hospital administration data to identify CRC. An interval cancer was defined as an invasive cancer diagnosed within 30 months of a negative screening result and before the next recommended examination. Gender, age, stage, and site distribution of interval cancers were compared with those in the screen-detected group. Results. Within the study period, 97 tumors were screen-detected and 74 tumors were diagnosed after a negative screening. In addition, 17 CRC (18.3%) were found after an inconclusive result and 2 cases were diagnosed within the surveillance interval (2.1%). There was an increase of interval cancers over the four rounds (from 32.4% to 46.0%). When compared with screen-detected cancers, interval cancers were found predominantly in the rectum (OR: 3.66; 95% CI: 1.51–8.88) and at more advanced stages (P=0.025). Conclusion. There are large numbers of cancer that are not detected through fecal occult blood test-based screening. The low sensitivity should be emphasized to ensure that individuals with symptoms are not falsely reassured.